How Anxious are Indonesians when They Can Travel Again Soon? - Imam Nur Hakim; I Dewa Gede Richard Alan Amory (Jurnal Ilmu Sosial dan Humaniora, 2022)
When traveling soon, Indonesia faces travel anxiety after experiencing travel restrictions during a pandemic. This study is dedicated to identifying how strong the level of anxiety is and the tactical steps Indonesian tourism policymakers can take. Through a quantitative approach, it was found that there were differences in the application of the theory of anxiety levels initiated by Peplau. However, through adjustments and theoretical extensions to the pandemic situation, this study identifies the readiness of the Indonesians by looking at their feelings of anxiety, which are primarily low and medium. As a result, Indonesians with mid-education levels, low incomes, and living in areas with low tourist movement tend to have low anxiety levels. Meanwhile, the best way to deal with Indonesian people who feel excessive anxiety is to direct them to natural attractions with appropriate amenities that can be reached by private vehicles in short trip durations.